Rethinking Capitalist Development - Mott, Tracy; Shapiro, Nina (Routledge Frontiers of Political Economy, 2005)
This collection honours the work of the eminent economist Josef Steindl. Steindl's work is illuminated through a critical appraisal of its central constructs with a focus on its relevance to current economic conditions. This collection charts the thinking of one of the leading economic theorists of the twentieth century.